Working with female offenders : a gender-sensitive approach - Van Wormer, Katherine S. (Hoboken, N.J. : John Wiley & Sons, 2010)
"Taking into account the special needs of girls and women within a system designed by men for male offenders, Working with Female Offenders offers counselors, correctional officers, lawyers, probation officers - in short, anyone who works in some capacity with female offenders - an evidence-based, gentler approach for working effectively and successfully with girls and women in trouble with the law." "Working with Female Offenders provides coverage devoted to the nature of female crime and to the institutional settings in which much of the female-specific programming is designed to take place. This timely volume equips professionals with proven counseling strategies tailored to fit this population."--Jacket.
A gendered approach -- Traditional and gender-sensitive treatment for delinquent girls -- The nature of women's crime -- Women in prison -- Gender-sensitive programming within institutional settings -- Counseling the female offender -- Teaching life skills and promoting healing -- Epilogue.
Includes bibliographical references (pages 263-289) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Women prisoners -- United States; Women prisoners -- Counseling of -- United States; Female offenders -- United States; z; x; Criminelles; SOCIAL SCIENCE -- Penology; Female offenders; Women prisoners; Women prisoners -- Counseling of; United States